Pictorial Review of Traumatic Pseudoaneurysm Treatment - Zangan, Steven M.; Tran, Patrick; Du, Jonathan (Digestive Disease Interventions, 2025)
Traumatic pseudoaneurysms develop due to disruption of the intima and media and lack an epithelialized wall; instead, there is a thin rim of fibrous tissue. While spontaneous thrombosis and regression have been described, traumatic pseudoaneurysms typically require treatment due to the high risk of rupture. As opposed to true aneurysms, pseudoaneurysm size is a poor surrogate for rupture risk. A variety of endovascular and percutaneous techniques exist to safely and definitively treat pseudoaneurysms. The goal is to exclude the pseudoaneurysm to eliminate the risk of rupture while avoiding nontarget embolization and preserving unexpendable arteries. In trauma scenarios, it is often difficult to have a complete evaluation of the relevant anatomy with key considerations including the pseudoaneurysm size and neck, the necessity of preserving the target artery, and the presence of collateral arteries. The following cases illustrate the variety of techniques available for pseudoaneurysm treatment, their relative merits, and key considerations.
Keywords: trauma; pseudoaneurysm; embolization